Śramika āndolana prasaṅge - Ghosh, Shibdas (Iu. Ṭi. Si. / (Lenina Saraṇī)-ra Paścimabaṅga Rājya Kamiṭi, 1979)
Speeches on Marxist approach to the labor movement in India by the leader of Marxist Leninist political party.